OBTAINING POSITIONS OF ASTEROIDS FROM DIGITIZED PROCESSING OF PHOTOGRAPHIC OBSERVATIONS IN BALDONE OBSERVATORY (CODE 069) - Eglitis, I.; Eglite, M.; Shatokhina, S. V.; Andruk, V. M. (Одеські астрономічні публікації, 2016)
Digital processing of photographic plates of star fields allows to determine with high accuracy the coordinates and stellar magnitudes for all registered objects on these plates. The processing results can be used for a broad search for images of small bodies of the Solar system and determination of their coordinates. From the observations of earlier epoch, we can extract information about the locations of these bodies well before discovering them. Modern approach to processing early photographic observations with new technologies can be an effective instrument for rediscovery of asteroids and correction their orbits. We analyzed the results of digital processing of observations of clusters in UBVR bands which were made on the 1.2-m Schmidt telescope of the Observatory of Institute of Astronomy ofUniversityofLatviain Baldone (code 069). As a result 87 images of minor planets from 9.8 to 17.1 stellar magnitude and 2 images of comets were identified on 152 plates for 1967-1996. The catalogue of positions and stellar magnitudes of the searching asteroids was compiled. Among them 12 observations of asteroids are the earliest of the world's known observations of these asteroids. All positions of asteroids were compared with the ephemeris JPL DE431. Analysis was carried out.